Apoptotic cells can induce non-autonomous apoptosis through the TNF pathway - Ainhoa Pérez-Garijo; Yaron Fuchs; Hermann Steller (eLife, 2013)
Apoptotic cells can produce signals to instruct cells in their local environment, including ones that stimulate engulfment and proliferation. We identified a novel mode of communication by which apoptotic cells induce additional apoptosis in the same tissue. Strong induction of apoptosis in one compartment of the Drosophila wing disc causes apoptosis of cells in the other compartment, indicating that dying cells can release long-range death factors. We identified Eiger, the Drosophila tumor necrosis factor (TNF) homolog, as the signal responsible for apoptosis-induced apoptosis (AiA). Eiger is produced in apoptotic cells and, through activation of the c-Jun N-terminal kinase (JNK) pathway, is able to propagate the initial apoptotic stimulus. We also show that during coordinated cell death of hair follicle cells in mice, TNF-α is expressed in apoptotic cells and is required for normal cell death. AiA provides a mechanism to explain cohort behavior of dying cells that is seen both in normal development and under pathological conditions.